2008
DOI: 10.1111/j.1439-0531.2007.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Usability of Butylated Hydroxytoluene in Conservation of Goat Semen

Abstract: The objective of this study was to investigate whether butylated hydroxytoluene (BHT) could be used as a suitable supporter or alternative of egg yolk during preservation of goat spermatozoa. Three in vitro experiments and a fertility test were conducted to evaluate the effect of BHT on viability of chilled-stored semen as well as motility and kidding rate of frozen-thawed spermatozoa. In the first two experiments, ejaculates (n = 30/experiment) were collected from 10 bucks, split, diluted with egg yolk-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
3
24
0
3
Order By: Relevance
“…However, owing to the paucity of literature regarding the use of antioxidants in canine species, the results need to be discussed in comparison to their use in other animals/ species. Similar improvements in semen quality by the use of BHT have been reported for turkey tom (Donoghue and Donoghue, 1997), cattle bull (Chaterjee and Gagnon, 2001;Shoae and Zamiri, 2008), ram (Watson and Anderson, 1983), goat (Khalifa et al, 2008), and boar (Roca et al, 2004) spermatozoa. The protective effect of antioxidant (BHT) is attributed to two mechanisms: firstly, the incorporation of the compound in the sperm membranes, hence, making them more fluidic and preventing them from the damage (Ijaz et al, 2009) and, secondly, declining the damaging potential of lipid peroxyl radicals by conversion into hydroperoxides (Thomassen et al, 2006).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, owing to the paucity of literature regarding the use of antioxidants in canine species, the results need to be discussed in comparison to their use in other animals/ species. Similar improvements in semen quality by the use of BHT have been reported for turkey tom (Donoghue and Donoghue, 1997), cattle bull (Chaterjee and Gagnon, 2001;Shoae and Zamiri, 2008), ram (Watson and Anderson, 1983), goat (Khalifa et al, 2008), and boar (Roca et al, 2004) spermatozoa. The protective effect of antioxidant (BHT) is attributed to two mechanisms: firstly, the incorporation of the compound in the sperm membranes, hence, making them more fluidic and preventing them from the damage (Ijaz et al, 2009) and, secondly, declining the damaging potential of lipid peroxyl radicals by conversion into hydroperoxides (Thomassen et al, 2006).…”
Section: Discussionsupporting
confidence: 54%
“…The damage inflicted on the sperm membrane during cryopreservation renders the membrane more permeable to the BHT metabolites which, in turn, has a harmful effect (Shoae and Zamiri, 2008;Sahashi et al, 2011). Similarly, BHT was found to be toxic for cattle bull (Shoae and Zamiri, 2008), goat (Khalifa et al, 2008), human (Aitken and Clarkson, 1988) and boar (Roca et al, 2004) spermatozoa. This toxicity is due to counteracting the ROS-induced oxidative stress by higher antioxidant levels, hence hampering those functions of spermatozoa which are associated with ROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of Uppsala extender and INRA-96 extender with 1 mM BHT did not improve post-thaw motility of dog sperm [16], which is 897 EFFECT OF BHT ON DOG SPERM STORAGE consistent with our findings. However, BHT has been demonstrated to maintain post-thaw sperm characteristics in many species [13,14,18,24]. Two mechanisms for protecting sperm by BHT have been suggested [10]: 1) BHT is incorporated into the sperm membrane, resulting in an increase of membrane fluidity, and 2) BHT prevents the activity of lipid peroxyl radicals by converting them to hydroperoxides.…”
mentioning
confidence: 99%
“…Supplementation of semen extenders with antioxidant compounds could overcome this problem. Butylated hydroxytoluene (BHT), a synthetic phenolic antioxidant, is not only commonly used as a food additive [26], but is also widely used for low-temperature preservation of mammalian [2, 3,11,13,14,17,18,24,25] and avian sperm [6]. It was reported that BHT suppressed sperm mitochondrial metabolism and protected the cell membranes from cold shock by decreasing oxygen toxicity in the bull [12].…”
mentioning
confidence: 99%